Efektivitas Sistem Manajemen Syariah dalam Pengelolaan Lembaga Keuangan - Ustwatun Hasanah; Dewi Sartika; Resta Yuliansih; Bekhlul Idana; M. Roychan Fachri; Jefry; Muhammad Gheza (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2025)
The Sharia management system is a governance approach for financial institutions based on Islamic values that prohibit usury (interest), gharar (uncertainty), and maysir (speculation). This system encompasses not only the regulation of financial products but also holistic governance practices, including organizational structure, decision-making processes, supervision, and performance evaluation guided by Islamic principles. This article aims to analyze the effectiveness of Sharia management system implementation in managing Islamic financial institutions in Indonesia, including both banking and non-banking sectors. A qualitative approach and descriptive method are used to explore how principles such as justice, trustworthiness, consultation, and social responsibility are embedded in managerial practices. Findings reveal that effectiveness is largely influenced by three main factors: the consistent application of Sharia principles, the competency of human resources, and the presence of strong internal and external oversight mechanisms. Despite its potential to provide ethical and sustainable financial solutions, Sharia management faces challenges including legal dualism, limited innovative product development, and low public literacy on Islamic finance. Therefore, strategic efforts such as managerial training, incorporation of Sharia management in higher education curricula, and supportive public policies are essential to enhance the effectiveness and resilience of Islamic financial institutions in the long term.